A fjord-like tropical ecosystem, Pacific coast of Costa Rica: overview of research in Golfo Dulce - Vargas-Zamora, José A. (2021)
Introduction: Coastal ecosystems worldwide are under the influence of local, regional and global stressors, such as pollution, eutrophication and climate change. Golfo Dulce is a relatively pristine and accessible deep tropical ecosystem that provides opportunities for comparative and collaborative research. Objective: To summarize published reports on past research conducted in this ecosystem, identify topics for further study, and suggest new research issues. Methods: A search was made on the web for reports based on research conducted in Golfo Dulce and published in scientific journals. Reports focusing on environmental parameters and on the biota were included. Results: A total of 123 studies that include data from Golfo Dulce are cited. The four topics more frequently addressed were reports based on the results of the R/V Victor Hensen expedition (1993-1994) and follow-up work on microbiology, studies on water parameters, research on vertebrates, and zooplankton studies. The reports focusing on vertical profiles of oxygen and temperature are discussed in detail, followed by those on the biota. Conclusions: Golfo Dulce has low oxygen concentrations below 50 m and is frequently anoxic at the 200 m deep basin with occasional formation of H2S. However, the ecosystem contains a relatively high diversity of identified organisms, from bacteria to whales. Of particular relevance for future studies are multidisciplinary surveys aiming at obtaining data on primary productivity, the diversity and biomass of the main groups of planktonic, demersal and benthic organisms, and the frequency and magnitude of the influx of deep offshore waters over the sill into the basin. These data, as well as the information gathered in the past, are essential for updating the trophic model developed more than 25 years ago and in support of new predictive models on the functioning of the ecosystem.